POLA PENGAJARAN YESUS DAN RELEVANSINYA BAGI PENGAJARAN GURU PENDIDIKAN AGAMA KATOLIK DI SEKOLAH-SEKOLAH DI KOTA MADIUN - Merri Andini; Robertus Joko Sulistiyo (Lembaga Penelitian STKIP Widya Yuwana, 2021)
The teaching pattern of Jesus is at the core of the teaching of teachers who teach Catholic Religious Education because Jesus in teaching is not just a formality but Jesus always teaches with love and love. The teaching pattern of Jesus should be imitated by all believers, including teachers. But in reality, it is not uncommon for teachers to encounter teachers in carrying out their profession only to the extent of fulfilling their teaching obligations. Based on these problems, the following problems were formulated: What is the relevance of the teaching pattern of Jesus for the teaching of Catholic Religious Teachers in schools in Madiun City. Through this research, it is expected to know the extent to which Catholic Religious Teachers apply the Jesus Teaching Pattern to their teaching.The results showed that some Catholic Religious Education Teachers have used Jesus' Teaching Patterns in their teaching, such as Catholic Religious Education Teachers in teaching have used parables, Catholic Religious Education Teachers in teaching see students as their own friends, similar to what Jesus did to followers. The progress felt by Catholic Religious Education Teachers after following Jesus' teaching pattern: Catholic Religious Education Teachers feel accepted by students, Catholic Religion Teachers carry out the profession as a form of service